Carta del Teniente H. R. Lee, "Commanding, Post of Lares" al "Adjutant general" - Todd, Roberto H.; Harry R. Lee (My University, 1899)
Petición de formas en blanco para "Summary Court"
Keywords: Puerto Rico. Office of the adjutant general.; Headquarters, Department of Porto Rico